2018
DOI: 10.1681/asn.2018040437
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Fibrosis in HNF1B-Related Autosomal Dominant Tubulointerstitial Kidney Disease

Abstract: Ablation of HNF-1 in renal epithelial cells leads to the activation of a Twist2-dependent transcriptional network that induces EMT and aberrant TGF- signaling, resulting in renal fibrosis through a cell-nonautonomous mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 71 publications
(93 reference statements)
4
49
1
1
Order By: Relevance
“…Previous studies from our laboratory have shown that ablation of Hnf1b in kidney epithelial cells and kidney-specific knockout of Hnf1b in transgenic mice lead to activation of the canonical Wnt pathway (24). To identify Wnt pathway genes that are directly regulated by HNF-1β, we compared our previous RNA-seq and ChIP-seq datasets (18) and identified Lef1, a downstream effector in the canonical Wnt signaling pathway, as a potential HNF-1β target gene. To determine whether expression of Lef1 is dependent on HNF-1β, we performed quantitative RT-PCR analysis on mIMCD3 cells in which Hnf1b was deleted by CRISPR/Cas9 gene editing (18).…”
Section: Expression Of Lef1 Is Increased In Hnf-mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies from our laboratory have shown that ablation of Hnf1b in kidney epithelial cells and kidney-specific knockout of Hnf1b in transgenic mice lead to activation of the canonical Wnt pathway (24). To identify Wnt pathway genes that are directly regulated by HNF-1β, we compared our previous RNA-seq and ChIP-seq datasets (18) and identified Lef1, a downstream effector in the canonical Wnt signaling pathway, as a potential HNF-1β target gene. To determine whether expression of Lef1 is dependent on HNF-1β, we performed quantitative RT-PCR analysis on mIMCD3 cells in which Hnf1b was deleted by CRISPR/Cas9 gene editing (18).…”
Section: Expression Of Lef1 Is Increased In Hnf-mentioning
confidence: 99%
“…To identify Wnt pathway genes that are directly regulated by HNF-1β, we compared our previous RNA-seq and ChIP-seq datasets (18) and identified Lef1, a downstream effector in the canonical Wnt signaling pathway, as a potential HNF-1β target gene. To determine whether expression of Lef1 is dependent on HNF-1β, we performed quantitative RT-PCR analysis on mIMCD3 cells in which Hnf1b was deleted by CRISPR/Cas9 gene editing (18). Under basal conditions, the expression of Lef1 was 4.7-fold higher in HNF-1β-deficient cells compared to wild-type mIMCD3 cells.…”
Section: Expression Of Lef1 Is Increased In Hnf-mentioning
confidence: 99%
See 1 more Smart Citation
“…EMT is essential for tissue regeneration and, when sustained, is associated with fibrogenesis 33 . Recently, Chan et al found that loss of HNF1b may induce EMT in vitro and in vivo, leading to upregulation of expression of TGF-b ligands in renal epithelial cells, which can ultimately cause renal fibrosis 34 . These findings reveal a potential novel mechanism of renal fibrosis in HNF1B-nephropathy 2,34. The second important finding of our study was that cystic disease was the predominant renal imaging phenotype, being found in 92% of patients (see Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identi ied novel post-transcriptional and post-translational regulatory mechanisms that control HNF-1β expression and activity, including the miRNA cluster miR17 ∼ 92 and the interacting proteins PCBD1 and zyxin. Further understanding of the molecular mechanisms upstream and downstream of HNF-1β may lead to the development of new therapeutic approaches in cystic kidney disease and other HNF1B-related renal disease [15][16][17].…”
Section: Discussionmentioning
confidence: 99%